Pengembangan Multimedia Integratif Bahasa Inggris untuk Siswa di Pendidikan Dasar - Wijirahayu, Suciana; Syarif, Mohammad Suryadi (Jurnal SOLMA, 2019)
A workshop on developing integrative media of English and math other subjects with songs as a model (You tube video) and the researches from UHAMKA Graduate School especially about peer assessment and the use of online comic maker are used as inspiration. Creativity of the workshop?s participant is expected tube developed and the result of the integrated media and other subjects especially in elementary school could be developed  continuously to create more conducive classroom. The skill of the participants in developing by cooperating in creating four prototypes integrated media in the form songs and video with different subjects (math, biology, natural science and environment). The participants who are involving are from different schools.